Research of potential of share certificates in the agricultural sector - Давиденко, Надія Миколаївна (Technology audit and production reserves, 2014)
The main national features of the enterprises of the agricultural sector were determined and strategic objectives of the agricultural sector of Ukrainian economy in order to ensure food security of the country were formed in the paper. The place of the state in forming the system of laws and regulations on the land market was defined. The level of financial support of the agricultural sector was characterized and it was found that most agrarian formations of various organizational-legal forms run a deficit of financial resources. The author proposes one of the sources of financial resources, in particular through share certificates. Issue of share certificates allows, on the one hand, to provide farm enterprises with financial resources, on the other, to mobilize local and regional securities markets, which in turn will have a positive impact on the situation in the countryside and domestic securities market. It was proposed to include share certificates in listing of local-regional securities markets.